The Need for and Possibility of a Christian Forgiveness Education in Schools. Issue 1 (2nd January 2018) - van der Walt, Johannes; de Muynck, Bram; Broer, Nico; Wolhuter, Charl; Potgieter, Ferdinand
ABSTRACT: Individuals and communities occasionally need asking and giving forgiveness. Because the process of forgiving is not always well understood, it has become necessary to consider including forgiveness education in school pedagogy and in formal school programs such as Citizenship Education. This possibility is illustrated with examples from South Africa and The Netherlands. To date, forgiveness education has mostly taken the form of brief research interventions. It is recommended that forgiveness education, also from a Christian viewpoint, be given a more prominent place in school curriculums as well as in teacher education programs.